Microwave denture disinfection versus nystatin in treating patients with well-controlled type 2 diabetes and denture stomatitis: A randomized clinical trial - Sanitá, Paula Volpato [UNESP]; Machado, Ana Lúcia [UNESP]; Pavarina, Ana Cláudia [UNESP]; Sgavioli Massucato, Elaine Maria [UNESP]; Colombo, Arnaldo Lopes; Vergani, Carlos Eduardo [UNESP] (My University, 2012)
Purpose: The aim of this randomized clinical trial was to compare the effectiveness of microwave denture disinfection and nystatin in the treatment of well-controlled type 2 diabetic patients with denture stomatitis in terms of microbiologic and clinical outcomes. Materials and Methods: Diabetic patients wearing maxillary complete dentures with denture stomatitis (n = 40) were divided into two groups: NYS (patients treated with topical nystatin 4 times/day for 14 days) and MW (patients who had their dentures microwaved [650 W for 3 minutes] 3 times/week for 14 days). Mycologic samples were taken from the palates and dentures of the patients for quantification and identification of Candida, and standardized photographs of the palates were taken for clinical analysis. Evaluations were repeated at baseline, the end of treatment (day 14), and throughout follow-up (days 30, 60, and 90). Microbiologic data were evaluated by analysis of variance using a random effects statistical model, Tukey post hoc test, and chi-square test (a = .05). Clinical resuts were analyzed using Mann-Whitney and Fisher exact tests (a = .05). Results: Both treatments were considered successful in reducing the clinical signs of denture stomatitis and significantly reduced the values of colony-forming units/mL from the palates and dentures at days 14 and 30. In addition, 40% of treated patients were cured by the end of treatment. No significant differences in the microbiologic and clinical outcomes were revealed between the two groups (P > .05). C albicans was the most predominant species isolated (P < .01), followed by C tropicalis and C glabrata. Conclusion: Denture microwave disinfection was as effective as nystatin for the treatment of diabetic patients with denture stomatitis. © 2012 by Quintessence Publishing Co Inc.